Empirical study on important elements of mobile augmented reality application for heritage content - Fatin Norsyafawati Mohd Sabri; Nik Zulkarnaen Khidzir; Ahmad Rasdan Ismail; Khairul Azhar Mat Daud (2016)
Lately, mobile device has become a convenient platform for augmented reality (AR). Day by days, mobile devices are getting popular as a platform for AR application such as a Smartphone. Mobile AR (MAR) is mainly available whenever people require an informational support for a focused task. However, only a limited number of researches are avalaible in the mobile augmented reality application. The objective of this study is to determine what are the important elements that need to be considered when designing animated infographic MAR application for heritage content. 300 samples have been distributed to the higher learning education students and lecturers with the return rate of 66.67%. The findings of the research show that the most important elements are color, slightly changes in text, touch screen, graphic user interface, dynamic picture and also static picture. This paper also highlight the reliability test of the research instrument where the result indicate that it is satble and reliable to use in conducting the survey. Through the findings, private companies, government institutions or multimedia developer would be able to identify important elements when designing mobile augmented reality application appropriately and effectively.